PRICE INTERDEPENDENCE IN THE INTERNATIONAL AND BRAZILIAN BEEF CATTLE MARKET - de Oliveira Neto, Odilon José; Santana Figueiredo, Reginaldo; Wander, Alcido Elenor (Revista Econômica do Nordeste, 2022)
The objective of this study is to verify the interdependence and asymmetry in price transmission between the main Brazilian and international slaughter beef cattle markets. We used for causality and cointegration tests, and the application of the multiple regression model to analyse the asymmetry in price transmission between the main Brazilian and international markets. The results showed that there is an interdependent relationship between the prices of live cattle in the Brazilian market and the prices of beef cattle in international markets. However, the direction of transmission between them is significant only from the prices of live cattle in the main Brazilian markets to the prices of beef cattle in international markets.